Second Language Acquisition (SLA) research implications for language teachers - Porto, Melina (2001)
The aim of this article is to examine whether instruction can facilitate SLA. Studies investigating the effects of instruction on the rate and ultimate level of attainment of SLA as well as on the route of development of acquisition are considered. The former confirm that tutored acquirers learn faster and reach higher levels of attainment than their naturalistic counterparts. The latter suggest that instruction is powerless to alter the sequence of SLA, except transitorily and in insignificant ways. Although more research is needed, the overall conclusion is that instruction does help. Some implications for classroom teaching in the area of syllabus design, teaching materials, practice, and input are explored. Considering that acquisition is not linear, it is suggested that a cyclical syllabus may offer teachers the flexibility they need to adapt teaching practices to their unique classroom cultures. Similarly, teaching materials, conceived as illustrations rather than as prescriptions for teaching, are not to be strictly adhered to but can be adjusted to suit the learners' needs. It is also claimed that practice in the form of information-gap and problem-solving activities, by combining linguistic repetition with a non-linguistic purpose, is beneficial. It may lead to the acquisition of formulaic language - pervasive in L1 and SLA and adult language use. Finally, it is suggested that in successful communication, input is graded automatically.